2022
DOI: 10.11591/ijeecs.v25.i3.pp1672-1678
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of named-entity effect on text classification of traffic accident data using machine learning

Abstract: <span lang="EN-US">With the rising number of accidents in Indonesia, it is still necessary to evaluate and analyze accident data. The categorization of traffic accident data has been developed using word embedding, however additional work is needed to achieve better results. Several informative named entities are frequently sufficient to differentiate whether or not information on a traffic accident exists. Named-entities are informational characteristics that can offer details about a text. The influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…The methods developed for Named Entity Recognition with machine learning include Hidden Markov Model (HMM) [7], Decision Tree [8], Maximum Entropy [9], Support Vector Machine (SVM) [10], Conditional Random Fields (CRF) [11], and Association rules mining [12], [13]. Current research on Indonesian Language for accuracy in Named Entity Recognition (NER) is still not maximized [14] due to the nature of the Indonesian Language because Indonesian has unique orthographic, morphological and p-ISSN: 2528-1682 e-ISSN: 2527-9165…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods developed for Named Entity Recognition with machine learning include Hidden Markov Model (HMM) [7], Decision Tree [8], Maximum Entropy [9], Support Vector Machine (SVM) [10], Conditional Random Fields (CRF) [11], and Association rules mining [12], [13]. Current research on Indonesian Language for accuracy in Named Entity Recognition (NER) is still not maximized [14] due to the nature of the Indonesian Language because Indonesian has unique orthographic, morphological and p-ISSN: 2528-1682 e-ISSN: 2527-9165…”
Section: Introductionmentioning
confidence: 99%
“…NER systems often have to deal with variations in language use, including different spellings, abbreviations, and contexts that can make it challenging to accurately identify and classify named entities in the Zakat domain. Not much research has been identified in Indonesia regarding the NER in Indonesian [10] compared to English [15]. Some issues related to Indonesian NER can be found in [12].…”
Section: Introductionmentioning
confidence: 99%